2021
DOI: 10.18280/ijsdp.160420
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Key Performance Indicators for Measuring Real Estate Project Success

Abstract: The purpose of this study is to find numerous key performance indicators for measuring real estate project success. A Systematic literature review was adopted to achieve the research objective. The main objective of a systematic literature review is to identify, evaluate, and synthesize existing research. A total number of "82" papers from ABDC journals and other journals and conference papers, including thesis, book chapters, were used to identify all the success factors. The study reveals that most of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…A major goal of project and program management is to meet cost and schedule targets. Rani et al (2021) argue that this is a traditional way to measure project success. However, project management success is an integral part of the project's overall success (Shenhar et al, 1997).…”
Section: Project Performancementioning
confidence: 99%
“…A major goal of project and program management is to meet cost and schedule targets. Rani et al (2021) argue that this is a traditional way to measure project success. However, project management success is an integral part of the project's overall success (Shenhar et al, 1997).…”
Section: Project Performancementioning
confidence: 99%
“…A study found 2026 articles on stakeholders in project management literature from 1984 to 2009 where most of the research was on construction projects originating from the UK, Australia, America, and Canada [13]. Many studies also have evaluated stakeholder relationships and project success [14]. Das and Ngacho [15] found that owner, consultant, and contractor factors were positively related to project success.…”
Section: Introductionmentioning
confidence: 99%